Evaluation of the quality and stability of amoxicillin oral suspension - Blanca Elena Ortega Markman, Maria Regina Walter Koschtschak, Elizabeth Wu Meihuey, Paulo Cesar Pires Rosa (Journal of Applied Pharmaceutical Science, 2014)
The laboratory control of diseases frequently receives powders for oral suspension of amoxicillin, with reports of therapeutic ineffectiveness and problems in reconstituting suspensions. The compendial analyzes not shows quality deviations. This fact motivated the study to assess the quality and stability of oral suspensions amoxicillin in the period of use corresponding to the first and seventh days after reconstitution. Six generic drugs were tested along with the referential drug during its intake period, from the first to the seventh day after powder reconstitution for suspension by high performance liquid chromatographic method. The reconstitution of all samples resulted in suspensions with homogeneous aspect. Both pH assay and amoxicillin identification complied with the product’s specification. The amoxicillin rates were determined in the 1th and 7th days after the reconstitution of samples through a method for stability detection, developed and validated before. At the 1th day, a generic drug sample presented 78% of the rate declared, below the lowest-value specification (90%). In the 7th day, 3 generic drug samples presented rates below 87%, 83% and 68.1% of the declared value, lower than the minimal specification, thus evidencing pharmacotechnical flaws in the product because of its lack of stability. Percent degradation rates of 3.5%, 4.0%, 6.0%, 9.9%, and 15% amoxicillin in 5 of the generic formulations studied are significant. The present study about amoxicillin oral suspension provides information about the stability during the using period, described for manufacturers. Even though the degradation products have not been identified, they can compromise their safe use, meaning potential risks to the users because of possible toxicity and/or therapeutic inefficacy.
Keywords: Amoxicillin oral suspensions, stability, generic drugs.